Essential Oils as Bioinsecticides Against Blattella germanica (Linnaeus, 1767): Evaluating Its Efficacy Under a Practical Framework - Ana Manzanares-Sierra; Eduard Monsonís-Güell; Crisanto Gómez; Sílvia Abril; Mara Moreno-Gómez (Insects)
Concerns about the negative effects of traditional insecticides and increasing insecticide resistance have prompted the exploration of botanical alternatives like essential oils (EOs). The registration of biocides is a mandatory procedure, and some regions have established a special status for compounds that meet specific low-risk criteria, which includes certain EOs. This study aimed to evaluate and compare the efficacy of sixteen EOs, both registered as low-risk biocides and/or standard biocides, against the German cockroach, Blattella germanica. A topical application was performed with undiluted EOs (15 µL) on the dorsal surface of awake cockroaches. The results showed significant variations in efficacy, as follows: thyme, sweet orange, and lavender oils were the most effective, achieving 100% mortality within 24 h and a less than 30 s knockdown effect. In contrast, linseed and cottonseed oils were the least effective, resulting in 70% and 40% 24 h mortality. Remarkably, some EOs registered as low-risk biocides performed as well as the ones registered as standard biocides, suggesting that this category does not have to always be at odds with efficacy. Future research should adopt practical, application-driven approaches to ensure bioinsecticides balance performance and safety, meeting both regulatory and consumer demands.